Решить систему уравнении а) 2x-y=2 2x^2-xy=6 б) (x+2)(y+1)=12 x+2y=6 в) x^2+y^2=10 xy= -3

Решить систему уравнении а) 2x-y=2 2x^2-xy=6 б) (x+2)(y+1)=12 x+2y=6 в) x^2+y^2=10 xy= -3
Гость
Ответ(ы) на вопрос:
Гость
2X - Y = 2 ; Y = 2X - 2  2X^2 - X * ( 2X - 2 ) = 6  2X^2 - 2X^2 + 2X = 6  2X = 6  X = 3  Y = 6 - 2 = 4  ОТВЕТ ( 3 ; 4 )  ----------------------------------- ( X + 2 )*( Y + 1 ) = 12  X + 2Y = 6 ; X = 6 - 2Y  ( 6 - 2Y + 2 )*( Y + 1 ) = 12  ( 8 - 2Y )*( Y + 1 ) = 12  8Y + 8 - 2Y^2 - 2Y = 12  - 2Y^2 + 6Y - 4 = 0  - 2 * ( Y^2 - 3Y + 2 ) = 0  D = 9 - 8 = 1 ; √ D = 1  Y1 = ( 3 + 1 ) : 2 = 2  Y2 = ( 3 - 1 ) : 2 = 1  X1 = 6 - 4 = 2  X2 = 6 - 2 = 4  ОТВЕТ ( 2 ; 2 ) ; ( 4 ; 1 )  --------------------------------------- X^2 + Y^2 = 10  XY = - 3  X = ( - 3 / Y ) ; X^2 = 9 / Y^2  ( 9 / Y^2 ) + Y^2 = 10  ( 9 + Y^4 ) / Y^2 = 10 ( Y ≠ 0 )  9 + Y^4 = 10Y^2  Y^4 - 10Y^2 + 9 = 0  Y^2 = A ; A > 0  A^2 - 10A + 9 = 0  D = 100 - 36 = 64 ; √ D = 8  A1 = ( 10 + 8 ) : 2 = 9  A2 = ( 10 - 8 ) : 2 = 1  Y^2 = 9 ===> Y (1 /2 ) = ( + / - ) 3  Y^2 = 1 ===> Y ( 3/4 ) = ( +/ - ) 1  X^2 = 9 / Y^2  X^2 = 9 / 9 = 1 ===> X ( 1/2 ) = ( + / - ) 1  X^2 = 9 / 1 = 9 ===> X ( 3/4 ) = ( + / - ) 3  ОТВЕТ ( 1 ;  3 );  ( - 1 ;  - 3  );   ( 3  ;  1 ) ;  ( - 3 ; - 1 ) 
Не нашли ответ?
Ответить на вопрос
Похожие вопросы